1979
DOI: 10.1159/000117701
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Homeostatic Fluctuations of Skin Temperature in the Sleeping and Waking State

Abstract: 53 healthy persons were monitored for skin temperature by a Hardy dermal radiometer every 60 sec. Readings continued until a spontaneous cycle appeared. 32 subjects were examined awake and 21 while asleep. A spontaneous rhythm with a mean of 4.25 min was found for the awake subjects, and one of 8.33 for the asleep subjects. To confirm these findings longer recordings were made by a thermocouple electronic thermometer in a further 23 subjects. Observations were continued until the awake subject slept. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2000
2000

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…What differences did exist did not relate to the physical characteristics of the subject but may have reflected rather his state of awareness. In another investigation (Lovett Doust, 1978) we have demonstrated an elongation of cycle length as the awake state gives place to drowsiness and sleep. Iberall ( 1972) in an extensive review coveringmany species of mammals concluded that the relative state of alertness was the principle reason for any discrepancies in thermorégulation observed in them.…”
Section: Discussionmentioning
confidence: 77%
“…What differences did exist did not relate to the physical characteristics of the subject but may have reflected rather his state of awareness. In another investigation (Lovett Doust, 1978) we have demonstrated an elongation of cycle length as the awake state gives place to drowsiness and sleep. Iberall ( 1972) in an extensive review coveringmany species of mammals concluded that the relative state of alertness was the principle reason for any discrepancies in thermorégulation observed in them.…”
Section: Discussionmentioning
confidence: 77%